Beyond decomposition: Processing zero-derivations in English visual word recognition. (July 2019) - Wheeldon, Linda; Schuster, Swetlana; Pliatsikas, Christos; Malpass, Debra; Lahiri, Aditi
Abstract: Four experiments investigate the effects of covert morphological complexity during visual word recognition. Zero-derivations occur in English in which a change of word class occurs without any change in surface form (e.g., a boat-to boat ; to soak-a soak ). Boat is object-derived and is a basic noun (N), whereas soak is action-derived and is a basic verb (V). As the suffix -ing is only attached to verbs, deriving boating from its base, requires two steps, boat(N) > boat(V) > boating(V), while soaking can be derived in one step from soak(V) . Experiments 1 to 3 used masked priming at different prime durations to test matched sets of one- and two-step verbs for morphological ( soaking-SOAK ) and semantic priming ( jolting-SOAK) . Experiment 4 employed a delayed-priming paradigm in which the full verb forms ( soaking and boating ) were primed by noun and verb phrases ( a soak/to soak, a boat/to boat ). In both paradigms, different morphological priming patterns were observed for one-step and two-step verbs, demonstrating that morphological processing cannot be reduced to surface form-based segmentation.